You are on page 1of 65

# 1

## set of all continuous functions from G to Ω, designated by C(G, Ω) is called space of

continuous functions.

....(1)

## Cover of a compact set ς{Kx ⊂}U

G1{U
GG 2 U
:G ς }U G n
∈....
n
A collection of set ς satisfying (1) is called cover of the compact set K.

## for every ε>0 there is an integer N such that d ( xn , xm ) < ε, ∀ n, m ≥ N

Complete metric space : A metric space (X,d) is called complete metric space

## if each Cauchy sequence has a limit in X.

Let G ⊂ C, G is an open subset of C and H(G) the set of all analytic functioins

## space of continuous functons from G to C.

2

H (G ) ⊂ C (G , C )

We denotes the set of analytic function on G by H(G) rather than A(G) because

## g continuous function that are analytic in G}

Thus A(G ) ≠ H (G )

## to f uniformly over T. Hence by Morera’s theorem

∫ f = lim ∫ f = 0
T T
...(1)

## since each f n is analytic.

→R = − | f n (w) − f (w) |
fr n k )}()→ ( z) ⊂
ffTnnf(((nkG
a {A
) f (k ) k!
z) −{f gf :( k, )G ≤ C; ∫γ | dw |
D 2π | w − z |k +1
γ G

## If we take a circle γ ≡| z − a |= R then by Cauchy’s Integral formula

k! ⎡ f n (w) f (w) ⎤
f n( k ) ( z) − f ( k ) ( z) = ∫ ⎢
2πi γ ⎣ (w − z) k +1

(w − z) k +1 ⎥⎦
dw ∀ z∈D

⇒ ...(2)

3

## | f n ( w) − f ( w) |≤ M n , then from the equation (2)

k! Mn
∴ f n( k ) ( z ) − f ( k ) ( z ) ≤ ∫
2π γ ( R − r )k +1
| dw |

k!M n k!M n
k +1 ∫
= | dw | = .2πR
2π ( R − r ) γ 2π ( R − r ) k +1

k!M n R
= for |z-a|<r ...(3)
2π ( R − r )k +1

## Since f n → f , and limMn = 0 then (3) gives

⇒ f n( k ) → f (k )
uniformly on B (a ; r ).

## from any of the boundary point of G is greater than r, i.e.

0 < r < d ( K , ∂G ) then in K such that
n
K ⊂ U B(a j ; r )
j =1
K

∂G
Since f n( k ) → f ( k ) uniformly on each{δ|∃nfzB
(≥=:−
az|(1N a,≠a−|=;20{|
)inf
za
j r)
R|f=(R
a,...., za)}n|:| z − a |= R} > 0

number δ as

## that if and then

δ
| f ( z ) − f n ( z ) |< <| f ( z ) |
2
≤| f ( z ) | + | f n ( z ) |
4

Thus from above it follows that f and fn satisfies the condition of Rouche’s

theorem.

## C (G , C ∞ ) then either f is meromorphic or f ≡ ∞ . If each f n is analytic then either

f is analytic or f ≡ ∞

a
f(a)
G
C∞

Now

....(1)

## But f n → f so there is an integer n{|Bf0zff∞n(a(−

,(z(})ffza1|∈C
such
nn a<|fthat
)(,|≤ −
); f|ρn| (f)fz(n)⊂a−
≤2|r∞,....} f)|((a−≤)f |(f+af(|n);
( )zB za|)+
af()(M ))−|≤| 2fM
( a )) || ∀ z ∈B(a; r) and n ≥ n0
ρ
d ( f n (a); f (a)) < , ∀n ≥ n0
2
Also the set is compact in C (G , C ∞ )

⇒ it is equicontinuous

## i.e. ∃ an r > 0 such that

ρ
⇒ d ( f n ( z ), f ( z )) <
2
ρ
⇒ d ( f n ( z ); f n (a)) <
2
This gives that d ( f n ( z ), f ( a ) ) ≤ ρ for | z − a |≤ r and for n ≥ n0

Now

⇒ ...(2)

## In view of the ρ chosen in (1); the expression (2) can be written as

.....(3)
5

2 | fn (z) − f (z) |
d ( fn (z) , f (z))=
But
{[1 + | f n ( z ) |2 ][1 + | f ( z ) |2 ]}
1/ 2

∀ z ∈ B (a ; r ) and n ≥ n0
2 | f n ( z) − f ( z) |

{(1 + 4M 2
)(1 + 4 M 2 )} 1/ 2

∀ z ∈ B (a ; r ) and n ≥ n0
Since d { f n ( z ), f ( z )} → 0 uniformly for z ∈ B (a; r ) this gives that
| f n ( z ) − f ( z ) |→ 0 uniformly for z ∈ B (a; r )

From (3)

## define 1/g as follows:

f (a ) = ∞
1 1
( z) = if g ( z ) ≠ 0 or ∞;
g g ( z)

1
( z) = 0 if g ( z ) = ∞; and
g

1
( z) = ∞ if g ( z ) = 0
g

1
Then it follows that ∈ C (G, C∞ )
g

Also, since f n → f in C (G, C∞ ) then by the property of metric over non zero

## complex number z1 and z2 , i.e.

⎛1 1 ⎞
⎟⎟ and d ( z,0) = d ⎛⎜ , ∞ ⎞⎟
1
d ( z1 , z 2 ) = d ⎜⎜ ,
⎝ z1 z 2 ⎠ ⎝z ⎠
1 1
It follows that f → f in C (G , C ∞ )
n

1
Now each f is meromorphic on G;
n
6

1 1
So, ∃ r > 0 and an integer n0 such that f and f are analytic on B(a; r) for
n

n ≥ n0

1 1
⇒ →
fn f uniformly on B(a; r).

1 1
From Hurwitz theorem, either ≡ 0 or has isolated zeros in B(a; r).
f f

1
∴ if f ≡/ ∞ then ≡/ 0 and f must be meromorphic in B(a; r)
f

Combining this with the result (4) that f is meromorphic in G if f is not identically

infinite.
1
If each fn is analytic then f has no zeros in B(a; r). Then [ corollary : {fn} ⊂
n

## H(G) converges to f in H(G) and each fn never vanishes on G then either f ≡ 0 or

1 1
never vanishes] then either f ≡ 0 or f never vanishes.
1
But since f (a ) = ∞ we have that f has at least one zero; thus f ≡ ∞ in B(a;r)
Fz −f{|a∈|f<F(r,z ) |:| z − a |< r , f ∈ F} < ∞

|sup
Thus, either f ≡ ∞ or f is analytic

## constants M and r >0, such that

| f ( z) |≤ M , for

Alternately
F is locally bounded if there is an r >0 such that

Montel’s Theorem

7

....(1)

## Since F is normal therefore a function and a subsequence such

that
f nk → f

⇒ sup{| f nR ( z ) − f ( z ) |: z ∈ K} → 0 as k → ∞

If | f ( z ) |≤ M for z ∈ K

n k ≤ sup{| f nk ( z ) − f ( z ) |: z ∈ K } + M

when nk → ∞
{ }
ff′∈
F
m
sup
H ≥G1))ffU
{|
((z
sup{| (G z∞
n) ({
nk to M which cannot be true (
right hand side converges
∈KK},≥ fn ∈ F} = ∞
) ||}::zz∈
∞≤M)
Hence the assumption taken at start is wrong. Therefore if is normal it is locally

bounded.

Corollary : is closed in C (G , C ∞ ) .

2 | f ′( z ) |
1+ | f ( z ) |2
....(1)

## increases the order of the pole. Therefore (1) is meaningless.

This can be rectify by taking limit of (1) as z approaches the pole. Now we show

that the limit of (1) when z tends to pole. Let ‘a’ be a pole of f of order ; then
8

## f(z) can be expressed as

Am A1
f ( z) = g ( z) + + .... +
( z − a) m
( z − a)
for z in some disk about a and g(z) analytic in that disk.

For z ≠ a

mAm A1
2 m +1
+ .... + − g ′( z )
2 | f ′( z ) | ( z − a) ( z − a) 2
=
∴ 1+ | f ( z ) | 2 Am A1
2

1+ + .... + + g ( z)
( z − a) m ( z − a)

2 | z − a | m −1 | mAm + ..... + A1 ( z − a ) m −1 − g ′( z )( z − a ) m +1 |
=
| z − a | 2 m + | Am + ..... + A1 ( z − a ) m −1 + g ( z )( z − a ) m | 2

Thus if m ≥ 2
2 | f ′( z ) |
lim =0
z → a 1+ | f ( z ) | 2
⎡ mAm A1 ⎤
f ′( z ) = g ′( z ) − ⎢ m +1
+ .... + ⎥
If m = 1 then ⎣ ( z − a) ( z − a) 2 ⎦

A1
2 − g ′( z )
2 | f ′( z ) | ( z − a) 2
lim = lim
z →a 1+ | f ( z ) | 2 z →a 2
A1
1+ + g ( z)
( z − a)

1
2 A1 − ( z − a) 2 g ′( z )
| z−a| 2
= lim
z →a 1
| z − a |2
[
| z − a | 2 + | A1 + g ( z )( z − a) | 2 ]
2 | A1 | 2
= 2
=
| A1 | | A1 |

2 | f ′( z ) |
which shows that for m ≥ 1 the limit of exits.
1+ | f ( z ) | 2
9

## Theorem : Riemann Mapping Theorem

Let G be a simply connected region which is not the whole plane and let

f D

f(G)
G C

## (a) f(a) = 0 and

(b) f is one-one

(c) f (G ) = {z :| z |< 1}

## g is one-one and ′:(|G

|afc∈ =aG)1→
=C0

g (G ) = {z :| z |< 1} g : G → D

## and D = {z :| z |< 1} then

1−1
g :G → D
onto
1−1
−1
and fog : D → D and analytic.
onto

−1

## Then by the theorem-

1−1
Let f : G → D analytic and f (a ) = 0 ∃ a complex number c with | c |= 1
onto

z −α
such that f =cϕα , ϕα (z) = 1 − α z is Mobious transformation.

## Implies that ∃ a constant c; and fog−1(z) = cz ∀z

⇒ f ( z ) = cg ( z )
10

## Since and cg ′(a) > 0

⇒ c =1

⇒ f=g

Hence f is unique.

For the existence of f, consider the family F of all analytic function f having

and a ∈ K n ∀ n

## Then { f ( K n )} is sequence of compact subsets of D = {z :| z |< 1} .

Also, as n becomes larger { f ( K n )} becomes larger and larger and tries to fill

## out the disk.

0gf∞f′=
|F
Choosing f ∈ F with the largest possible (< = ) c: gf ′ (isa );one− one, f (a) = 0, f ′(a) > 0, f (G) ⊂ D}
′01(0aH)(G
(aaz{))f>|><∈
U Kf (nderivative
K=n G ) = D at a, we choose the function
n =1
which “starts out the fastest” at z =a.

Thus

Lemma : Let G be a region which is not the whole plane and such that every

## (a) f(a) = 0 and

(b) f is one-one

(c) f (G ) = D = {z :| z |< 1}

## Proof : Let we define F as

Since f (G ) ⊂ D then
11

proved that

....(1)

## Suppose (1) and (2) hold and consider the function

f → f ′(a ) of H (G) → C

## This is a continuous function and since F − is compact there is a f in with

F.
Since (empty set) therefore f ∈ F .

## Suppose w ∈ D such that ff ≠

,F
w
F ′∉
then φ)fthe
−( za −
≥w
(G ′( a ) ∀g ∈
g)function
1 − w f ( z)
is analytic in G and never vanishes.

## then by the hypothesis there is an analytic function h : G → C which is equal to

the square root of a analytic function, i.e.
f ( z) − w
[h( z )] 2 = ....(3)
1 − w f ( z)

## Since the Mobious transformation

ς −w
Tς = maps D onto D, h(G) ⊂ D.
1 − wς

Define g : G → C by
| h ′(a ) | h( z ) − h(a )
g ( z) = . ....(4)
h ′(a ) 1 − h(a ) h( z )

Then | g (G ) |≤ 1 ⇒ g(G) ⊂ D,
12

Also

## | h′(a) | h′(a)[1− | h(a) |2 ]

g ′(a) = .
h′(a) [1− | h(a) | 2 ]2
| h′(a) |
=
1− | h(a) | 2
But
f (a) − w 0 − w
| h(a) |2 = = =| −w |=| w |
1 − wf (a) 1 − 0

## and derivative of (3) gives

f ′( z ) (1 − w f ( z )) − ( f ( z ) − w) ( − w f ′( z ))
2h( z )h′( z ) =
[1 − w f ( z )]2
f ′( a ) − w w f ′( a )
2 h ( a ) h ′( a ) =
1
2h(a )h ′(a ) = f ′(a )(1− | w | 2 ) egf h((azz ))) =≠=0f0( z )

f ′(a)(1− | w | 2 ) 1
∴ g ′(a) = .
2 | w| 1− | w |

⎛ (1+ | w |) ⎞ ⎡ 1+ | w | ⎤
= f ′(a)⎜ ⎟ ⎢Q > 1⎥
⎜ 2 | w| ⎟
⎝ ⎠ ⎣⎢ 2 | w | ⎥⎦

> f ′(a )

## This contradict that g is in F and the choice of f. Thus f(G) = D.

Theorem : Let f(z) be analytic in a simply connected region R and suppose that

f(z) has no zeros in R. Then there is a analytic function h(z) such that for

all z ∈ R .

Proof : Since in R
f ′( z )
then f ( z ) is also analytic in R and therefore for any two points a and z in R the
13

integral

....(1)

## Let α be an argument of f(a) then f(a) can be expressed as

f (a) = r eiα and set

## β = log | f (a) | +iα

e β = elog|f (a)|+iα
= e log| f ( a )|
e i α = e log r
e iα = r e iα
Then e β = f (a) ...(2)

and if we consider

f ′(ς )
z
h( z ) = β + ∫ dς ....(3)
a
f (ς )

## We get h(a ) = β , then from (2) we have

F (′(zz)z)=ff e(′(fzhς)(′(z)−)z )F ( z ) f ′( z ) = 0
hIF′=(z) =
e h(a ) β
= e = f (a)
∫ f (fς ()z)dς ...(4)
a

## ⇒ h(z) is analytic in R for all z ∈ R

from (3)

Let F ( z) = e h( z )
f ′( z )
then F ′( z ) = e h′( z ) = F ( z ) f ( z )
h( z )

F ′( z ) f ′( z )
⇒ =
F (z) f ( z)

F ′( z ) f ( z ) − F ( z ) f ′( z )
⇒ =0
[ F ( z )]2

Q be non vanishing
14

d ⎛ f ( z) ⎞
⇒ ⎜ ⎟=0
dz ⎜⎝ F ( z ) ⎟⎠

f ( z)
⇒ = κ (a constant ) for all z ∈ R
F ( z)
Putting z =a, we obtain

∴ f ( z ) = F ( z ) = e h( z )

The analytic function h(z) defined as above is called logarithm of f(z) in R and

we write h( z ) = log f ( z ) .

## Clearly, if h(z) is a logarithm of f(z), then (m an integer) is also

logarithm of f(z).

## Convergence of logarithm series :

zn z 2 z )z+3
πi f (a) f (a)
log(1 + z) = ∑(−1) n−1 = z − κh(=
+ f (2a−m
)......
n=1 n 2 F 3 (a) = h(a) = f (a) = 1
e

## If |z| < 1 then

log(1 + z ) ⎛ z z2 ⎞
1− = 1 − ⎜⎜1 − + − ... ⎟⎟
z ⎝ 2 3 ⎠

z 1 2 ⎛1 1 ⎞
= − z + .... ≤ ⎜ | z | + | z | 2 +....⎟
2 3 ⎝2 3 ⎠
1
≤ (| z | + | z | 2 +.....)
2
1 |z|
≤ ....(1)
2 1− | z |
1
Further if | z |< then
2
log(1 + z ) 1
1− ≤
z 2
15

z − log(1 + z ) 1
⇒ ≤
z 2
|z|
⇒ | log(1 + z ) | − | z |≤
2
3
⇒ | log(1 + z ) |≤ |z|
2
1
Since log (1+z) is converges to 1, then for | z |< , we have
2
|z| 3
≤| log(1 + z) |≤ | z | ....(2)
2 2

Proposition :
∞ ∞
Re z n > 0 ∀n ≥ 1 . Then ∏ z n converges to a non-zero number iff. ∏ log z n
n =1 n =1

converges.

## Proof : Let pn = ( z1 ⋅ z 2 ⋅ z3 ⋅ .... ⋅ z n )

m = =p≥niθkn=0n z=− π
, nre
kzlim
m∞ k<θ<π
n→

## then exp( S n ) = exp[log z1 + log z 2 + ..... + log z n ]

= exp[log( z1 .z 2 .... z n )] = p n

## ∴ S n = ln( p n ) + 2πik n for some integer kn.

Now suppose

, then

S n − S n −1 = log z n → 0

## Also ln( p n ) − ln( p n −1 ) → 0

Hence ( k n − k n −1 ) → 0 as n → ∞

## Since kn is an integer, there exists integers n0 and k such that

for
16

So S n → ln( z ) + 2 πiK

Corollary :

## If Re z n > 0 then the product. ∏ z n converges absolutely iff the series

∑ ( z n − 1) converges absolutely.

Lemma :

Let X be a set and f1, f2, f3 ... be functions from X into C such that

## f n ( x) → f ( x) uniformly for x in X. If there is a constant ‘a’ such that

Re f ( x) ≤ a ∀x ∈ X then exp f n ( x ) → exp f ( x ) uniformly for x in X.

## Now choose n0 such that

{δnexp[
ge≥>nz }0n−0ffn1n((|x< −a
ε−neexp
x))− |<εεee−−aa | exp f ( x) |≤ ε
| f n ( x ) − f ( x ) |< δ ∀x ∈ X ||whenever
exp ≥f (nx0f)](−x)1|<

exp f n ( x)
⇒ − 1 < εe − a
exp f ( x)

Lemma :

## Let (X, d) be a compact metric space and let be a sequence of continuous

function from X into C such that ∑ g n (x) converges absolutely and uniformly for x in
17

X.

Then the product f ( x) = ∏ (1 + g n ( x)) converges absolutely and uniformly for
n =1

n, 1 ≤ n ≤ n 0

## integer n0 such that and n ≥ n 0

3
⇒ and | log(1+ gn (x)) |≤ | gn (x) |; ∀ n ≥ n0 and x ∈ X
2

Thus h( x) = ∑ log(1 + g n ( x)) converges uniformly for x∈ X
n = n0 +1

Now

∴ is also continuous.

## Q X is compact ⇒ h(x) must be bounded. x))<C≠a(0X∀, Cx)∈ X

g (hxh()(x∈
exp
Re f ( x11) +=
log(
Re[ + [gg1 +1((xxg)]))(>x0)][1 + g ( x )]......[1 + g n ( x )]. exp h( x )
| gn n ( x) |<nn 1∀ x ∈ X 2
In particular, there is a constant a such that 2

Then

⎡ ∞ ⎤
exp h( x) = exp ⎢ ∑ log(1 + g n ( x))⎥
⎣ n = n0 +1 ⎦

= ∏(1+ gn (x)), converges uniformly for x ∈ X and
n=n0 +1

for any x ∈ X .

Now if we take

then

f (x) = ∏(1+ gn (x)),
n=1
18

## Definition : An Elementary factor is one of the following function or

E( z ; p)
for p = 0, 1, 2, 3,... defined as

E(z ; 0) or E0 (z) = 1 − z

⎛ z2 zp ⎞
E( z ; p) or E p ( z ) = (1 − z ) exp⎜⎜ z + + .... + ⎟, p ≥ 1
⎝ 2 p ⎟⎠

⎛ 2 p

; p ) or E p ⎛⎜ z ⎞⎟ = ⎛⎜1 − z ⎞⎟ exp⎜ z + 1 ⎛⎜ z ⎞⎟ + ...... 1 ⎛⎜ z ⎞⎟ ⎟, p ≥ 1
z
E(
a ⎝a⎠ ⎝ a⎠ ⎜a 2⎝a⎠ p ⎝ a ⎠ ⎟⎠

⎛z⎞
⇒ E p ⎜ ⎟ has a simple zero at z =a and no other zero.
⎝a⎠
Also if b is a point in C − G then

## ⎛a−b⎞ ⎛ a −b⎞ ⎡ a − b 1 ⎛ a − b ⎞2 1 ⎛a−b⎞ ⎤

p
Ep⎜ ⎟ = ⎜1 − ⎟ exp ⎢ E (z+) ⎜ ⎟ + .... + ⎜ ⎟ ⎥
⎝ z −b⎠ ⎝ z −b⎠ ⎣⎢ z −pb 2 ⎝ z − b ⎠ p ⎝ z − b ⎠ ⎦⎥

Lemma

## For a fixed p let the power series expansion of E p (z ) about z =0 is

E p ( z) = 1 + ∑ ak z k ....(1)
k =1

## differentiating (1), we have

E ′p ( z ) = 1 + ∑ k a k z k −1
k =1

## From the definition of Ep (z)

19

⎛ z2 zp ⎞ ⎛ z2 zp ⎞
E ′p ( z ) = −1 exp⎜⎜ z + + .... + ⎟ + (1 − z ) exp⎜ z +
⎟ ⎜ + .... + ⎟(1 + z + z 2 + .... + z p −1 )
⎝ 2 p ⎠ ⎝ 2 p ⎟⎠

= exp⎜⎜ z +
z2
+ .... +
zp ⎞
[
⎟ − 1 + (1 − z )(1 + z + z 2 + .....z p −1 )
p ⎟⎠
]
⎝ 2

On simplifying expressiion in the square bracket only z p remains and all other terms

## will cancelled out.

∞ ⎛ z2 zp ⎞
∴ ∑ k k a z k −1
= − z p
exp ⎜
⎜ z + + ..... + ⎟
p ⎟⎠
k =1 ⎝ 2

## On comparing coefficients of like power of z, we find that

a1 = a 2 = .... = a p = 0

⎛ z2 zp ⎞
exp⎜ z + + ..... + ⎟ are all positive
Also the coefficient of the expression of ⎜ p ⎟⎠
⎝ 2

## a k ≤ 0 for k ≥ p + 1E′ = −z p exp⎛⎜ z + z + .... + z ⎞⎟

2 p
, therefore
p ⎜ p ⎟⎠
⎝ 2
Thus | a k |= − a k for k ≥ p + 1

⇒ E p (1) = 0 = 1 + ∑ an
k = p +1

∞ ∞
or ∑ | ak | = − ∑ ak =1
k = p +1 k = p +1

Hence for | z |≤ 1

| E p ( z ) − 1 |= ∑ ak z k
k = p +1

=| z | p +1 ∑ a k z k − p −1
k = p +1

≤ | z | p+1 ∑ | ak |
k= p+1

=| z | p +1
20

Proposition

## Let Re z n > −1 then the series ∑ log(1 + z n ) converges absolutely iff ∑ z n

converges absolutely.

## Proof : If ∑ | z n | converges then z n → 0

1
⇒ | z n |<
2
1 3 1
Since | z | ≤ | log(1 + z ) | ≤ | z | for | z |<
2 2 2
1
Therefore for | z n |< the series ∑ | log(1 + z n ) | is convergent.
2
Conversely if, ∑ | log(1 + z n ) | converges then
1
| z n |<
2
∴ ∑ | z n | is converges

## Absolute convergence of an infinite product.

∏ | z n | converges / ∏ z n converges

Example: Let Z n = −1 ∀ n ∏ zn
then | z n |= 1 ∀ n

⇒ ∏| z n | converges to 1.
n
However ∏ z k is ± 1 depending on whether n is even or odd,
k =1

## Given an infinite sequence of complex numbers a 0 = 0, a1 , a 2 ,...., a n with no finite

point of accumulation, the most general entire function having zeros at those points

## only (a zero an n ≥1 of multiplicity α being repeated α times in the sequence) is given

21

by
∞ ⎛ z

F ( z) = e h( z ) m
z ∏ E ⎜⎜ a
; k n ⎟⎟ ...(1)
n =1 ⎝ n ⎠
where h(z) is an arbitrary entire function, m ≥ 0 is the order of multiplicity of a0

=0, and the kn are non negative integers such that the series
k n +1

z

n =1 an
...(2)

## 0 <| a1 |≤| a 2 |≤| a 3 |≤ ....

with | a n |→ ∞

The sequence { k n } of non-negative integers can always be found such that the

## We may take k n +1 = n , since

n
z 1 z 1
≤ or ≤ ...(3)
an 2n an 2

as soon as | a n |≥ 2 | z | which for any given z holds for sufficiently large value of

n , say n>N

## ⇒ N depends on |z| ⇒ pointwise convergence.

Since we are not interested in uniform convergence, only point wise convergence.

## From the already proved result that

1
if | z |≤ < 1 then
p
p
log E( z; k ) ≤ | z |k +1 ...(4)
p −1

then for p =2
log E ( z ; k ) ≤ 2 | z | k +1

provided
22

1
| z |≤
2
We have y
k +1
⎛ z ⎞ z an
log E ⎜⎜ ; k ⎟⎟ ≤ 2
⎝ an ⎠ an
provided Z
x
O R 2R
z 1

an 2

⇒ | a n |≥ 2 | z |

Let R be an arbitrary positive number and consider two circles with centres at

## Hence the series

⎛ z | a |> 2 R

is absolutely and uniformly convergent for all∑
n
z, such ⎜ |z|;<k nR,⎟ and it follows that the
log Ethat ⎜a ⎟
|a n | > 2 R ⎝ n ⎠
product

⎛ z ⎞
∏ E ⎜⎜ ; kn ⎟⎟
|a n |> 2 R ⎝ an ⎠

## Since the product

⎛ z ⎞
∏ E ⎜⎜ ;kn ⎟⎟
|a n |≤ 2 R ⎝ an ⎠
contain a finite number of factors each of which is an analytic function, it follows that
⎛ z ⎞
f1 ( z ) = ∏ E ⎜⎜ ;kn ⎟⎟
|a n |≤ 2 R ⎝ an ⎠

is analytic in |z| < R and vanishes in the disc only at those points of the sequence a1, a2,

## Then from the theorem : If f k ( z ); k = 1,2,... are analytic in open set

23

A ⊂ C, ∑| f (z) | is uniformly convergent on every compact set K ⊂ A , then
n=1
k

## converges absolutely in A to F(z) which is analytic in A.

We have

⎛ z ⎞
f2 (z) = ∏ E ⎜⎜ ; k n ⎟⎟
|a n | > 2 R ⎝ an ⎠
is analytic and different from zero in |z| < R.

## Hence the product

⎛ z ⎞
f ( z ) = f1 ( z ) f 2 ( z ) = ∏ E ⎜⎜ ; kn ⎟⎟
n =1 ⎝ an ⎠
is also analytic in |z| <R and vanishes in this region only at those points of the sequence

## a1 , a 2 .... which lie in there.

R was arbitrary chosen positive number, so that f(z) is analytic in the whole finite
∞ ∞
⎛ z⎞
place. ∏
sin π(1z += ef kg (( zz) )z.)∏ ⎜1 − ⎟e z / n ; n≠0
k =1 n = −∞⎝ n⎠
⇒ It is an entire function and has less zero precisely at the points a1 , a 2 ...., a n ...

∴ F ( z) = eh(z) z m f ( z)
is most general entire function with the prescribed zeros.

πz :
Factorization of sinπ

## sin πz is an entire function with simple zeros at 0, ± 1, ± 2,...

Then by Weierstrass factorization theorem the most general form of this entire

function be

⎡⎛ z⎞ ⎛ z⎞ ⎤
= e g ( z ) z .∏ ⎢ ⎜ 1 − ⎟ e − z / n ⎜ 1 + ⎟ e z / n ⎥
n =1 ⎣ ⎝ n⎠ ⎝ n⎠ ⎦
24

⎛ z2 ⎞
= e g ( z ) z ∏ ⎜⎜ 1 − 2 ⎟⎟ ...(1)
n =1 ⎝ n ⎠

## Taking logarithmic differentiation of (1)

⎡ ⎤
( )

d
π cot πz =
dz ⎢

g ( z ) + log z + ∏
n =1
log( n 2 − z 2 ) − log n 2 ⎥

1 ∞ ⎛ 2z ⎞
= h′( z ) + +∏⎜ ⎟ z ≠ ±n ...(2)
z n =1 ⎝ z 2 − n 2 ⎠

But ...(3)

## Let e C = C1 then (1) gives

⎛ z2 ⎞
sin π z = C 1 z ∏ ⎜⎜ 1 − 2 ⎟⎟
n =1 ⎝ n ⎠

sin πz C1 ∞ ⎛ z 2 ⎞
= ∏⎜⎜1 − 2 ⎟⎟ ; z≠0
πz π n=1 ⎝ n ⎠ ∞
1 ⎛ 2z ⎞
Taking z → 0 π cot πz = + ∏ ⎜ 2 ⎟
n =1 ⎝ z − n ⎠
2
z
C1 n
⎛ k2 ⎞
1= lim lim ∏ ⎜⎜1 − 2 ⎟⎟
π z → 0 n → ∞ k =1 ⎝ n ⎠

⎛ z2 ⎞
Since ∏ ⎜⎜1 − n 2 ⎟⎟ is uniformly converges, therefore the order of limit can be
n =1 ⎝ ⎠

changed

C1 n
⎛ z2 ⎞
= lim lim ∏ ⎜⎜1 − 2 ⎟⎟
π n → ∞ z → 0 k =1 ⎝ k ⎠
C n C
∴ 1 = π nlim
1
∏ (1) = π1
→ ∞ K =1

⇒ C1 = π

⎛ z2 ⎞
⇒ sin π z = π z ∏ ⎜⎜ 1 − 2 ⎟⎟
n =1 ⎝ n ⎠
25

Gamma function

According to Weierstrass (the weierstrass fact. th) the Γ function can be defined

as the reciprocal of a particular entire function with simple zeros at the points 0, -1, -

2,.. namely

⎛ z⎞
F ( z ) = e γ z z ∏ ⎜1 + ⎟e − z / n
n =1 ⎝ n⎠
−1
1 e−γ z ∞ ⎛ z ⎞ z / n

F(z)
= Γ(z) = ∏⎜1+ ⎟ e
z n=1 ⎝ n ⎠
...(1)

## z =0, -1, -2,...

Existence of γ
Now we show that there exists such γ.
Γ∞((1z) )=∞1e⎛−1 log C1−1⎞∞−1 ⎛ 1 ⎞ −1
eΓγ(1=)⎛⎜=∏ z⎞
∏ 1 +⎜11+⎟ n .⎟e∏z /e⎜n1 + n ⎟ e
1/ n 1/ n

n =1 ⎝ n ⎠
n =1 ⎝ ⎠
substituting z =1 in the infinite product n =1 ⎝ ⎠ , we get

∞ −1
⎛ 1⎞
∏ ⎜1 + n ⎟ e 1 / n = C a finite positive number ...(2)
n =1 ⎝ ⎠

1
= .C = 1
C

...(3)

## Hence the existance of γ is acertained.

26

Lemma :
1 1 1
Let H n = 1 + + + ... then γ = nlim
→∞
( H n − log n)
2 3 n
Proof : Taking logarithm on both sides of
∞ −1
⎛ 1⎞
e γ = ∏ ⎜1 + ⎟ e 1 / k
k =1 ⎝ k⎠
We have
∞ ⎡⎛ 1 ⎞ 1/ k ⎤
−1
γ = ∑ log ⎢⎜1 + ⎟ e ⎥
k =1 ⎢⎣⎝ k⎠ ⎥⎦

∞ ⎡⎛ k ⎞ 1 / k ⎤
= ∑ log ⎢⎜ ⎟e ⎥
k =1 ⎣⎝ k + 1 ⎠ ⎦
n
⎡ 1⎤
= lim ∑ ⎢log k − log(k + 1) + ⎥
k =1 ⎣ k⎦
n →∞

⎡ ⎤
⎢ n ⎥
= lim ⎢∑ {log k − log( kΓ (+z )1=)}lim + ∑ ⎥ n!.n
n
1 z

## n→∞ ⎢ 144 42444 3n → ∞ kz=(1z k+ 1⎥)( z + 2).....( z + n)

k =1
⎢ ⎧⎪ log1= 0 and all int ermediate ⎫⎪
⎨ terms will cancelled out except ⎬

⎢⎣ ⎪⎩ log (n +1) ⎪⎭ ⎥⎦

⎡ ⎛ 1 1 ⎞⎤
= lim ⎢− log(n + 1) + ⎜1 + + ... + ⎟⎥
n →∞
⎣ ⎝ 2 n ⎠⎦

⎡ ⎛ 1 1⎞ ⎤
= lim ⎢log n − log(n + 1) + ⎜1 + + ... + ⎟ − log n ⎥
n→∞
⎣ ⎝ 2 n⎠ ⎦

⎡⎛ 1 1⎞ ⎛ ( n + 1) ⎞⎤
= lim ⎢⎜1 + + ... + ⎟ − log n − log⎜ ⎟⎥
n →∞ ⎝ n⎠ ⎝ n ⎠⎦
⎣ 2

⎡⎛ 1 1⎞ ⎤ ⎡ ⎛ (n + 1) ⎞ ⎤
⇒ γ = lim ⎢⎜1 + + ... + ⎟ − log n − 0⎥ ⎢Q nlim log⎜ ⎟ = 0⎥
n→∞ ⎝ n⎠
⎣ 2 ⎦ ⎣ →∞ ⎝ n ⎠ ⎦

⇒ γ = lim ( H n − log n)
n→∞

## From the definition of Γ ( z )

27

−1
e −γ z n
⎛ z⎞
= lim ∏ ⎜1 + ⎟ e z / k
z n→∞ k =1 ⎝ k ⎠

e−γ z n
kez / k
= lim∏
z n→∞ k =1 ( z + k )

⎛ z z z⎞
e −γ z (1.2.3....n ). exp ⎜ z + + + .... + ⎟
= lim ⎝ 2 3 n⎠
n→∞ z ( z + 1)( z + 2).....( z + n )

⎧ ⎛ 1 1 1 ⎞⎫
e − z ( H n −log n ) .n!.exp⎨ z⎜1 + + + .... + ⎟⎬
= lim ⎩ ⎝ 2 3 n ⎠⎭
n →∞ z ( z + 1)( z + 2).....(z + n)

n!.e − zH n .e − z log n .e zH n
= lim
n →∞ z ( z + 1)( z + 2).....( z + n)

n!.n z
Γ ( z ) = lim e −γ z ∞ nz!.n−1z +1
n→∞ z )n=) lim ∏ ⎛⎜ 1 + ⎞⎟ e z / n
z ( z + 1)( z + 2).....(Γz( +
...(5)
n →z∞ ( z + 1)( z +n2).....( z + n + 1)
n =1 ⎝ ⎠

## Replacing z by (z+1) in the equation (5)

n! nz nz
= lim
n→∞ z( z +1)(z + 2).....(z + n) ( z + n +1)

n! n z z
= lim lim
n→∞ z ( z + 1)( z + 2).....(z + n) n→∞ z + 1
( + 1)
n

= Γ(z) . z
28

Reflection formula

## Proof : Using Euler’s formula

⎡ ( n! ) 2 .n ⎤
= lim ⎢ ⎥
n → ∞ z (1 − z )( 2 − z ).....( n − z )( n + 1 − z )
2 2 2 2 2
⎣ ⎦

⎡ ⎤
⎢ ⎥
⎢ 1 ⎥
= lim
n →∞ ⎢ ⎛ z 2
⎞ ⎛ z ⎛ n +1− z ⎞ ⎥
2

⎢ z (1 − z )⎜⎜1 − 2 ⎟⎟.....⎜⎜1 − 2 ⎟⎟⎜ ⎟⎥
2

⎣ ⎝ 2 ⎠ ⎝ n ⎠⎝ n ⎠⎦

1
=
⎧ ⎛ z2 ⎞ ⎛ z 2 ⎞⎫
z lim ⎨(1 − z 2 )⎜⎜1 − 2 ⎟⎟.....⎜⎜1 − 2 ⎟⎟ ⎬.1
n→∞
⎩ ⎝ 2 ⎠ ⎝ n ⎠⎭
π
z)z=) = lim ⎡; z ≠ 0, ±n1,!.±n2,... ⎤ ⎡
1 z
1 ΓΓ e(1(−1−
((szz)=) ΓΓ s log n

n!.n
= ∞ n sin πz ⎢ ⎥. lim ⎢
n →∞ z ( z + 1)( z + 2).....( z + n) n →∞ (1 − z )( 2 − z
⎛ z2 ⎞ ⎣ ⎦ ⎣
z ∏ ⎜⎜1 − 2 ⎟⎟
k =1 ⎝ n ⎠

1
=
sin πz
z.
πz
π
=
sin πz

∞ an
∑ s ....(1)
n =1 n

29

## If a n = 1, ∀n then the series (1) becomes

1
ς (s) = ∑ s , Re s = σ > 1
n=1 n

## represents Zeta function of Riemann.

Theorem : The series ∑ n
−s
converges absolutely and uniformly for σ ≥ 1 + ε
n =1

(ε > 0 arbitrary)

Proof : We have

1 1 1 1 1
= = = ≤
ns | nσ +it | | nσ | | nit | nσ n1+ε
∞ 1
and the series ∑ 1+ ε converges, by Weiestrass M-test
n =1 n

## Theorem : For Re s > 1

t s −1
Γ( s ) ς ( s) = ∫ dt
0
et − 1

t s −1 ∞

Proof : The integral ∫ t dt converges at both the lower and upper limits
0 e −1

whenever Re s > 1

Since
t
lim =1
t →0 + e −1
t

so that by the definition of limit there is a δ > 0 such that for 0 < t ≤ δ the

inequality
t 1
−1 < ε =
e −1
t
2

t 1
⇒ −1<
e −1 t
2
30

t 3
⇒ < holds.
e −1 2
t

## Hence for 0 < δ1 < δ and σ = Re s > 1

δ δ

t σ −2
e −1
t
3
t dt ≤ ∫ t σ − 2 dt =
2 δ1
3 1
2 σ −1
δ σ −1 − δ 1σ −1 ( )
δ1

δ
t σ −2 σ −1
⇒ ∫e t dt → 3 δ as δ1 → 0
δ1
t
−1 2 σ −1

## on the other hand, we have

tm
lim =0
t → +∞ e t − 1

tm 1
So that there is a b1, such that for t ≥ b1 the ineuqality t < is satisfied
e −1 2

## Hence for 0 < b1 < b and choosing m > σ we get

t m sσ − m −−1nu s −11 b σ − m −1
( )
b
1 1
1 1 ∫ e t) −=1nt ∫ e dtu≤ 2du∫ t
Γ ( s dt =
σ −
b σ − m − b1σ − m
→ b1σ −m as b → ∞ b1 0 b1 2 m
2 m−σ

−t s −1
Now in Γ( s) = ∫ e t dt
0

## which is valid for σ > 0 , we make the substitution t =nu to obtain

⎛ ⎞
⎜ N
N ∞⎟
1
Γ( s )∑ s = ∫ ∑ e
⎜ − nu ⎟ s −1
u du
and n =1 n ⎜ = ⎟
⎜ 123 ⎟
0 n 1

⎝ ( sum of G . P ) ⎠
∞ ⎛ −u
e (1 − e − Nu ) ⎞ s −1
= ∫ ⎜⎜ ⎟u du
0⎝ (1 − e −u ⎟⎠
∞ ∞
u s −1 u s −1 e − Nu
= ∫
0
eu − 1
du − ∫
0
eu − 1
du
31
Now it is required to prove that

u s −1e − Nu
∫0 eu − 1 du → 0 as N → ∞

∞ s−1 −Nu δ ∞
u e us−1e−Nu us−1e−Nu
∫0 eu −1 du= ∫0 eu −1 du+ ∫δ eu −1 du; δ >0

∞ δ ∞
u s −1e − Nu u σ −1 u σ −1
∫0 e u − 1 ∫0 e u − 1 ∫δ e u − 1 du
− Nδ
⇒ du < du + e

For a given ε >0, we choose δ sufficiently small so as to make the first integral
ε
on right hand side less than .
2
Fixing that δ we can now take N large enough so as to make the second term on

## the right less than

∴ for N → ∞

u s −1
Γ( s ) ς ( s ) = ∫ du valid for Re s >1
0
eu − 1
Note:B(E) denotes a closed algebraU
|rb∃ of−
ab,∈=V0C(K, dK1(D)
|<− <
aC<r that
) contains every rational
a, Kε
function with a pole in E 2

Lemma

If a ∈C − k then ( z − a) −1 ∈ B( E )

Proof : Case I : ∞ ∉ E

## Let and let

V = {a ∈ C : ( z − a)−1 ∈ B( E)}
so E ⊂V ⊂U

⇒ V is open

## | b − a |< r | z −a | ; ∀ z ∈K. ...(2)

32

But

−1
⎡ b−a⎤
= ( Z − 1) −1 ⎢1 − ⎥ ...(3)
⎣ Z − a⎦

From (2)

## | b−a| | z−a| −1<r <1; ∀z∈K. which implies that

−1
⎡ b−a⎤ ⎛b−a⎞
∞ n

⎢1 − z − a ⎥ = ∑⎜ ⎟ ...(4)
⎣ ⎦ n =0 ⎝ z − a ⎠

By the Weirestrass M-Test series on right hand side of (4) converges uniformly

on K.

⎛b−a⎞
n k

If Qn ( z ) = ∑ ⎜ ⎟ then
k =0 ⎝ z − a ⎠

( z − a ) −1 Qn ( z ) ∈ B ( E )

Since a ∈ V and B(E) is an algebra (3) shows that B(E) is closed and uniformly

## convergence of (4) implies that {b(az∈n−}∂b

V)−1 ∈ B((zE−
⎡ ) a ) − (b − a ) ⎤
−1

( z − b ) −1 = ⎢ ⎥ ( z − a)
−1

⎣ z−a ⎦

⇒ b ∈V

b = lim a n
n→ ∞

## | b − a n |≥ d ( a n , K ) then for n → ∞ ; an → b ; we get

0 = d ( b , K ) or b∈ K

## Thus ∂ V I U = φ ( null set )

If H is a component of U = C − K then H I K ≠ φ

So H IV ≠ φ
33

∴ H ⊂V

Case 2 :

## Let a0 is in the unbounded components of U = C − K such that

1
d ( a 0 , ∞) ≤ d ( ∞, K )
2
and | a0 |> 2 max{| z |: z ∈ K } ...(5)

## If a∈C− K then case-I gives that ( z − a ) −1 ∈ B ( E0 )

1
Now | z / a0 |≤ ; ∀z∈K [from (5)]
2
Therefore
1 1 1 ∞
=
z − a 0 − a 0 (1 − z / a 0 )
=− ∑
a0 n =0
( z / a0 ) n
U∞
E 0n∞∈
C
Q ⊂∈
=−E
V(BKE(E−){∞}) U {a 0 }
Converges uniformly on K.

Then
n
1
Qn ( z ) = −
a0
∑ (z / a
k =0
0 ) k is a polynomial

and ( z − a0 ) −1 = u − lim Qn on K.

## Since Qn has its only pole at ∞ ,

Thus ( z − a0 ) −1 ∈ B ( E )

⇒ B(E0 ) ⊂ B(E )

⇒ ( z − a) −1 ∈ B( E ) for each a ∈ C − K
Definition : Function element is a pair (f,G) where G is a region and f is an

analytic function on G.

Definition : Germ of f at a : [ f ]a .

34

## collection of all function elements (g, D) such that a ∈ D and in a

neighbourhood of a.

## Definition : Analytic continuation along a path.

Let γ :[0,1] → C be a path and suppose that for each t in [0,1] there is a function

(a) γ (t ) ∈ D

## (b) for each t in [0,1] there is a δ > 0 such that | s − t |< δ

⇒ γ ( s ) ∈ Dt and [ f s ]γ ( s ) = [ f t ]γ ( s ) (i.e. germ of fs and ft at γ(s) are equal)

## Power series method of analytic continuation

( z))≡let
Lemma : Let γ :[0,1] → C be a pathRfand
(t =∞g ({(z )f ∀ z
t , Dt ) : 0 ≤ t ≤ 1} be an analytic

continuation along γ. For 0 ≤ t ≤ 1 let R(t) be the radius of convergence of the power

continuous.

## Proof : If R(t ) = ∞ for some value of t then it is possible to extend ft to an entire

function.

Since

f s ( z ) = f t ( z ) ∀ z ∈ Ds

⇒ R ( s ) = ∞ ∀ s ∈ [0,1]

i.e. R (s ) ≡ ∞

35

let

## Let δ1 > 0 be such that | s − t |< δ1

⇒ γ ( s ) ∈ Dt I B ( τ; R (t ))

and [ f s ] γ ( s ) = [ f t ] γ ( s )

## If fs has a power series expansion

f s ( z ) = ∑ σ n ( z − σ) n about z = σ
n =0

then the radius of convergence R(s) must be at least as big as the distance from
z((τ−
RsR
|B (ss;)τt)R≥
−|−
<= t δR
(dR ∞
R(σ
)) t)t,))≤{D
(t(U | |z≤γ:|(|tzγ) −
(−t )τγ−|(=sγ)R(|s()t )})
| ≥ R (t ) − | τ − σ |
σ to the circle f t ( z ) = ∑1 τ n ( zs − τ) n
n =0

i.e.

⇒ R (t ) − R ( s ) ≤| γ (t ) − γ ( s ) |

Hence for

## Since γ :[0,1] → C is continuous.

⇒ R must be continuous at t.

## that meets each component of C ∞ − K . If f is analytic in an open set containing K and

ε>0 then there is a rational function R(Z) whose only poles lie in E and such that

| f ( z ) − R ( z ) |< ε ∀z∈K
36

Proof : By the fact that if K be a compact subset of the region G, then there are

straight line segments γ 1 , γ 2 ,.....γ n in G – Ksuch that for every function f in H(G).
n
1 f ( w)
f ( z) = ∑ ∫ dw ∀z ∈ K
K =1 2πi γ k w − z

## The line segments form a finite number of closed polygons.

Also If γ be a rectifiable curve and let K be compact set such that K I {γ} = φ .

If f is continuous function on {γ} and ε>0 then there is a rational function R(z) having

## Definition : Unrestricted analytic continuation :

Let (f, D) be a function element and let G be a region which contains D: then (f,

D) admits unrestricted analytic continuation in G if for any path γ in G with initial point

{γ}along γ.
in D there is an analytic continuation of (f, D)
f ( w)
∫ w − z dw − R( z ) ; ∀z ∈ K
γ

## Definition : If γ 0 , γ 1 :[0,1] → G are two rectifiable course in G such that

γ 0 (0) = γ 1 (0) = 0 and γ 0 (0) = γ 1 (0) = b then γ 0 and γ 1 are FEP homotopic if there is

a continuous map

Γ : I 2 → G such that

Γ ( s ,0 ) = γ 0 ( s )

Γ ( s,1) = γ 1 ( s )

Γ(0, t ) = a

Γ(1, t ) = b

for 0 ≤ s, t ≤ 1

I 2 = [0,1] × [0,1]
37

## γ 0 and γ 1 are fixed-end-point homotrpic in G then

[ f 1 ]b = [ g1 ]b

## ⇒ there is a continuous function

Γ :[0,1] × [0,1] → G such that

## Γ(t ,0) = γ 0 (t ) Γ(t ,1) = γ 1 (t )

Γ(0, u) = a; Γ(1, u) = b

## for all t and u in [0, 1]

b] b==
Let γ u (t ) = Γ(t , u ) for a fix u, 0 ≤ u ≤[h1f1,1,0]from [ h[a
1h, 10to
,1]b] b.
p ....(1)

along γ u

## and {( g t , Bt ) : 0 ≤ t ≤ 1} be analytic continuations along γ such that [ f 0 ] a = [ g 0 ] a . Then

[ f 1 ]b = [ g1 ]b

## Then it follows that

[ g1 ]b = [ h1,1 ]b and

...(2)

To show this

38

Since

## with | γ u (t ) −σ (t ) |< ε , ∀ t and if to any continuation of (f,D) along σ,

then
[h1,u ]b = [ K1 ]b ....(5)

## Suppose u ∈ U and let δ > 0 be the number given in (4). By definition of U,

,u tδ δv1,]0)b]∈b=δU⇒
(v0hu∈
|u
[u
, this implies U is open. If{( −
:∈U
G
1K
,|1−<U
[U0]v,→
b,Eu =[]t Rδ[+1≠
h)} h,and [is u0 ]∈bchoosen
h1,as U; above, then

∃a such that

## But form (4)

[h1,u ]b = [h1,v ]b ; and

since

⇒ U is closed

## a closed disk contained in G. If γ is the circle centred at a and of radius r i.e. γ :| z − a |= r

then
1 2π iθ
u (a) = ∫ u (a + re )dθ
2π 0
Proof : Let D be a disk such that
39

B (a; r ) ⊂ D ⊂ G, and

## Then by Cauchy integral formula

1 f (z)
f (a) = ∫
2π i γ z − a
dz

| z − a |= r
z = a + re iθ
dz = ir iθ
1 2 π f (a + re iθ )
=
2π 0
∫ re iθ dθ

1 2π iθ
= ∫ f (a + re )dθ
2π 0

1 2π iθ
f (a) = ∫ f (a + re )dθ
2π 0

1 iθ
Then Re f ( a) = 2π ∫ Re f (a + re )dθ
0 A = {Z ∈ G :u ( z ) = u (a)}

1 2π
⇒ u (a) = ∫ u ( a + re iθ )dθ
2π 0

## Definition : A continuous function u : G → R has the MVP if whenever

B (a; r ) ⊂ G
1 2π
u (a) = ∫ u ( a + re iθ )dθ
2π 0

40

## ∴ By continuity in the neighbouhood of b

If | z 0 − b |= ρ and b = z0 + ρe iθ 0 ≤ θ ≤ 2π

## then there is a proper interval I of [0, 2π] such that θ ∈ I and

Hence by MVP

1 2π
u ( z0 + ρe iφ ) dφ < u ( z0 )
2π ∫0
u ( z0 ) =

## So B( z0 ; r ) ⊂ A and A is also open.

by connectedness of G, A = G.

## Harmonic function on a disk : uuz 0((bzz∈) <

A u (aiφ) =<u+u((re
zz00i)θ)∀
0 + ρe ⎛) 1 ⎞∀z φ ∈ I 1 − r 2
Pr (θ ) = Re⎜⎜ iθ ⎟
⎟=
Study of harmonic function on a disk, open unit⎝ disk 1 − re{z − 2r cos θ + r 2
:⎠ |z| 1<1}

## Definition : Poisson Kernel : The function

Pr (θ) = ∑ r |n| e inθ
n = −∞

Theorem :

## Let z = re iθ , 0 ≤ r < 1 then

1 + reiθ 1 + z
⇒ iθ
= = (1 + z )(1 − z ) −1
1 − re 1− z
= (1 + z )(1 + z + z 2 + ....)

= 1 + 2∑ z n
n =1
41

= 1 + 2 ∑ r n e inθ
n =1

⎛ 1 + re iθ ⎞ ∞
⇒ Re⎜⎜

iθ ⎟
= 1 + 2 ∑ r n cos nθ
⎝ 1 re ⎠ n =1

(e inθ + e − inθ )
= 1 + 2∑ r n
n =1 2

= ∑ r |n| e inθ
n = −∞

= Pr (θ) ....(1)

Also

## 1 + re iθ (1 + re iθ )(1 − re −iθ ) 1 + re iθ − re −iθ − r 2

= =
1 − re iθ | 1 − re iθ | 2 | 1 − re iθ | 2

(1 − r 2 ) + r (i 2 sin θ)
=
| 1 − re iθ | 2

⎛ 1 + re iθ ⎞ 1− r2
⇒ Re⎜⎜ iθ
⎟=
⎟ 1 − 2r cos θ + r 2 ....(2)
⎝ 1 − re ⎠
[Q| 1 − reiθ |2 = 1 − 2r cos θ + r 2 ]

## Combining (1) and (2), we get the result.

Prop. 2.3
1 π
(a) ∫ Pr (θ)dθ = 1
2π − π
(b) Pr (θ) > 0 ∀θ, Pr ( −θ) = Pr (θ) and Pr is periodic in θ with period 2π.

## function. Then there is a continuous function u : D − → R such that

(a) u ( z ) = f ( z ) ∀ z ∈ ∂D

(b) u is harmonic in D.

## Moreover u is unique and is defined by the formula

1 π
u (re iθ ) = ∫ Pr (θ − t ) f (e )dt
it
for 0 ≤ r < 1, 0 ≤ θ ≤ 2π
2π − π
42

Proof : Define u : D → R as
1 π
u (re iθ ) = ∫ Pr (θ − t ) f (e )dt
it
for 0 ≤ r < 1 ...(1)
2π − π

## If 0 ≤ r < 1 then from (1)

1 π ⎡1 + rei ( θ−t ) ⎤
u (re iθ ) =
2π −∫π ⎣1 − re i ( θ−t ) ⎦
it
Re ⎢ ⎥ f (e )dt
1442443
by definition of Pr ( θ )

⎧⎪ 1 π it ⎡1 + re
i ( θ −t )
⎤ ⎫⎪
= Re⎨ ∫
⎪⎩ 2π − π
f ( e ) ⎢ i ( θ −t ) ⎥ ⎬
dt
⎣1 − re ⎦ ⎪⎭

⎧⎪ 1 π ⎡ e it + re iθ ⎤ ⎫⎪
= Re⎨ ∫
⎪⎩ 2π − π
f (e it ) ⎢ it iθ ⎥ ⎬
dt ...(3)
⎣ e e∂ε−Dαre0 ∃ a⎪ ρ, 0 < ρ < 1
i>
⎦ ⎭
Let us define g : D → C by

1 π it ⎡ e + z ⎤
it

2π −∫π
g ( z) = f ( e ) ⎢ it ⎥ dt ...(4)
⎣e − z ⎦

## Then g is analytic and

Re g = u ...(5)

∴ ∇ 2u = 0 ⇒ u is harmonic.

(ii) Continuity of u on D–

## If α ∈ [− π, π] and and an arc A of about such that for

ρ < r < 1 and e iθ in A

43

## Since f is continuous at z = 1 ∃ a δ > 0 such that

ε
| f (e iθ ) − f (1) |< if | θ |< δ ...(7)
3
Let {
M = max | f (e iθ ) | :| θ |≤ π }
Then from the result on Poisson kernel Pr (θ) < Pr (δ) if 0 < δ <| θ |≤ π

## There exists a ρ, 0 < ρ < 1 such that

...(8)

δ
for ρ < r < 1 and | θ |≥
2

iθ ⎧ δ⎫
Let A be the arc ⎨e :| θ |< ⎬ then if
⎩ 2⎭
e iθ ∈ A and ρ < r < 1
1 π
u (re iθ ) − f (1) = ∫ Pr (θ − t ) f (e )dt − f (1)
it
2π − π
ε
Pr (θ) <
3M
1 1
= ∫ Pr (θ − t )[ f (e it ) − f (1)]dt + ∫ Pr (θ − t )[ f (e ) − f (1)]dt
it
2π |t |< δ 2π |t |≥ δ

δ δ
if | t |≥ δ and | θ |≤ then | t − θ |≥
2 2
1 1
| u (re iθ ) − f (1) |≤ ∫ 2π |t |∫≥δ
Pr (θ − t ) | f (e it ) − f (1) | dt + Pr (θ − t ) | f (e it ) − f (1) | dt
2π |t |< δ

ε ε
≤ + 2M . [from (7) and (8)]
3 3M
⇒ | u (re iθ ) − f (1) |< ε

## Hence for general value of α.

| u ( re iθ ) − f (e iα ) |< ε ...(9)

44

## then (u-v) is harmonic is D and (u − v)( z ) = 0. ∀z ∈ ∂D

⇒ u-v=0

⇒ u is unique.

Harnack inequality

## If u : B (a; R) → R is continuous, harmonic in B(a; R) and u ≥ 0 then for 0 ≤ r < R

and all θ
R−r R+r
u (a) ≤ u ( a + re iθ ) ≤ u (a)
R+r R−r

## u n (z ) → ∞ uniformly on compact subset of G or {u n } converges in Har(G) to a

harmonic function.

## Let {u n } be a sequence in Har(G) such that

un → u in C (G, R)

⇒ u is harmonic

## [by the theorem if u : G → R which has MVP then u is harmonic.]

(b) Assuming u1 ≥ 0

## Let u ( z ) = sup{( u n ( z ) : n ≥ 1}; ∀ z ∈G

⇒ Either u (z ) = ∞ or u (z ) ∈ R and u n ( z ) → u ( z ), ∀ z ∈ G

Define
A = {z ∈ G : u ( z ) = ∞} ....(1)
45

B = {z ∈ G : u ( z ) < ∞} ...(2)

Then A U B = G and A I B = φ

## Then by Harnack’s inequality

R− | z − a | R+ | z − a |
u n (a) ≤ u n ( z ) ≤ u n (a) ; ∀ z ∈ B (a; R) and ∀ n ≥ 1.
R+ | z − a | R− | z − a |

...(3)

If a ∈ A then

⇒ B ( a; R ) ⊂ A

⇒ A is open.

## Similarly : If a ∈ B then right half of (3) gives

(a(a); <
that
)∞⊂∞B
uB(z )R→
Bn(a; R) ⊂ G
for | z − a |< R

⇒ u n (z ) < ∞ ∀ z ∈ B ( a; R )

⇒ B is open

## Since G is connected, either A =G or B =G

Suppose A = G; that is u ≡ ∞

## If and 0 < ρ < R then

( R − ρ)
M= > 0 and
R+P
(3) gives that

Mu n ( a ) ≤ u n ( z ) for | z − a |≤ ρ

46

## ⇒ u n (z ) → ∞ uniformly for z in any compact set.

Now suppose B= G

i.e. u( z) < ∞ ∀ z ∈G

If ρ < R then there is a constant N, which depends only on a and ρ such that

for | z − a |≤ ρ and ∀ n

So if

≤ C[u n ( a ) − u m ( a )]

## function [by part (a)]

Since u n ( z ) → u ( z )

⇒ ϕ
0m:(≤aG
B≤
Mu
u is the required harmonic function. nu;(nr→
n a())z⊂)≤R

Gu u,n (mz()z≤) ≤NNu
u n n( a( a) ) − Mu m ( a )

Definition :

such that

1
ϕ (a) ≤ ∫
2π 0
ϕ (a + reiθ )dθ

Definition:

such that

1
ϕ (a) ≥ ∫
2π 0
ϕ (a + reiθ )dθ
47

Definition :

## family denoted by Ρ ( f , G ) consists of all subharmonic function ϕ : G → R such

that

Dirichlet Problem : It consists in determining all regions G such that for any

## (b) lim ψ r ( z ) = 0 azzf ∈

ψ̂
w
lim :∈
(∈r G
)∂∞=G
a∂∂ψ
G
sup →
−I
r (ϕ
G0{B(R
zw ) f−(aa|)= r} ∀a ∈ ∂ ∞ G
)(za:=); |1r≤w
z→a z → aw

(c) for

If we define ψ̂ r by letting

ψ̂ r = ψ r on G(a; r)

ψˆ r ( z ) = 1 for
then is superharmonic.

## ⇒ ψ̂ r approaches the function which is one everywhere but at z=a, ψ̂ r is

zero.

Theorem : Let G be a region and let a ∈ ∂ ∞ G such that there is a barrier for G
at a.

## If f : ∂ ∞G → R is continuous and u is the Perron function associated with f then

lim u ( z ) = f ( a )
z→a

48

## | f ( w) |< ε whenever w ∈ ∂ ∞ G and

| w − a |< 2δ ;

Let ψ = ψδ

Let ψˆ : G → R defined by

## ψˆ ( z ) =ψ ( z ) for z ∈ G (a; δ ) and

for z ∈ G − B (a; δ ) ...(1)

Then is superharmonic.

## If | f (w) |≤ M for all w in ∂ ∞ G ...(2)

then

− Mψˆ − ε is subharmonic.

## Consider − Mψˆ − ε in Ρ ( f , G ) ....(3)

ψ
ϕ

ψ
∂ψ̂ (ϕG
−ˆ∞M
If w ∈ ∂ ∞ G − B (a; δ ) then from (1) and ∈
ψ ε )≤ u ( z ) ; ∀ z ∈ G
)ˆ=≥(Ρz1(0)f−, G
z(2)

z→w

Because

## ⇒ lim sup[− Mψˆ ( z ) − ε ] ≤ −ε ∀ w ∈ ∂ ∞ G ....(5)

z→w

If particular if w ∈ ∂ ∞ G I B ( a; δ ) then
lim sup[− Mψˆ ( z ) − ε ] ≤ −ε < f ( w) by the choice of δ.
z →w

## ⇒ the consideration (3) is valid.

Hence

...(6)

Similarly
liminf[Mψˆ ( z) + ε ] ≥ limsup(ϕ( z)) and w in .
z →w z →w

49

we have

∀ϕ in and z ∈ G

Hence

....(7)

## Since ε is arbitrary (8) implies

lim u ( z ) = 0 = f (a )
Z →a

Harmonic function

## continuous partial derivatives and satisfying the Laplace equation, i.e.

∂ 2u ∂ 2u Ρ(=(zf)ψ
+ = 0. or ∇ 2u = 0 ϕvψ̂
ulim ,ˆm≤G
Isup zϕ
(fM))ψ= z ) +ψ
≤ˆ (lim ε(;ψ
inf z)
∂x 2 ∂y 2 z→
→wa zz→
→wa

Harmonic conjugate

## and are called harmonic conjugates.

1 p k +1
Theorem : If | z |≤ p < 1 then | log E ( z; k ) |≤ p − 1 | z | .
Proof : Let k > 0
⎛ z2 zk ⎞
log E ( z ; k ) = Log (1 − z ) + ⎜⎜ z + + ..... + ⎟⎟
⎝ 2 k ⎠

z2 zk 1 k +!
Log (1 − z ) = − z − − − z ....
2 k k +1
for | z |< 1
1 k +1 1 1
∴ log E ( z; k ) = − z − z k + 2 − ..... for | z |≤ p < 1
k +1 k+2
50

⎛ 1 1 ⎞
∴ | Log E ( z; k ) |≤| log E ( z; k ) |≤ | z |k +1 ⎜ + | z | +...⎟
⎝ k +1 k + 2 ⎠
≤| z | k +1 (1+ | z | + | z | 2 +.....) [Q k > 0]

⎛ 1 1 ⎞
≤ | z | k +1 ⎜⎜1 + + 2 + ... ⎟⎟
⎝ p p ⎠
p
= | z | k +1
p −1
for k =0
⎛ |z| ⎞
| log E ( z;0) |=| log(1 − z ) |≤| z | ⎜1 + + ...⎟
⎝ 2 ⎠

⎛ 1 1 ⎞
≤ | z | ⎜⎜ 1 + + 2 + ... ⎟⎟
⎝ p p ⎠
p
| log E ( z;0) |= |z|
p −1

for p =2
2
| Log E ( z; k ) |≤ | z |k +1 = 2 | z |k +1
2 −1
1
provided | z |≤
2
Example : construct an entire function with simple zeros at the point
0, 1, 2 p , 3 p , ... , n p , ... ( p > 1)
Solution : We may take kn = 0 for every n. The series
∞ ∞
z 1
∑ n p
=| z | ∑ p
n =1 n =1 n

## ∴ by Weierstrass factorization Theorem

51

1
m=1 (simple zero at z=0), kn = 0, an =
np

⎛ z ⎞
⇒ F ( z ) = e h ( z ) z ∏ ⎜1 − p ⎟
n =1 ⎝ n ⎠

## Then by Weierstrass factorization Theorem

....(1)

k n +1

z
provided ∑
n =1 an
converges for ∀z where a n , n ≥ 1 are zeros.

k n +1
∞∞
⎛ ⎛z z ⎞ ⎞

r F ( zπ)z==e he( z ) z mz∏
sin h( z) 1
∏ E⎜⎜E ⎜⎜ ; k;n k⎟⎟ n ⎟⎟
since ∑
n = −∞ an
< ∞; n ≠ 0, ∀ r > 0 n =n1 =1 ⎝ a ⎝n a n ⎠ ⎠

## Then it is sufficient to choose k n = 1, ∀ n,

2

z ⎛ 1 1 1 1 ⎞
then ∑
n = −∞ an
=| z |2 ⎜ 2 + 2 + 2 + 2 + .... ⎟
⎝1 1 2 2 ⎠
n≠0

1
= 2 | z |2 ∑ n2 that conveyes for each z
n =1

## ∴ in (1) we may put a n = ± n, k n = 1 to get

⎛ z ⎞
sinπz = e h( z )
z∏E⎜ ; 1⎟
n=1 ⎝ ± n ⎠

⎡⎛ z ⎞⎛ z ⎞ ⎛ z ⎞ ⎛ z ⎞⎤

sinπz = e h( z )
z∏ ⎢⎜1+ ⎟⎜1 − ⎟ exp⎜ ⎟ exp⎜ − ⎟⎥
n=1 ⎣⎝ n ⎠⎝ n ⎠ ⎝ n ⎠ ⎝ n ⎠⎦
52

⎛ z2 ⎞
sin πz = e h( z )
z∏ ⎜⎜1 − 2 ⎟⎟
n =1 ⎝ n ⎠
Example : Construct an entire function with simple zero at the point 0, -1, -2,

...., -n.

## Solution : Given that an = -n then the series

k n +1

z

n =1 an
be convergent if kn =1

k n +1
∞ ∞ ∞
z 1 1
i.e. ∑
n =1 an
=| z | ∑
2

n =1 | −n |
2
=| z |2 ∑n
n =1
2

## Then Weierstrass factorization Theorem gives

∞ ⎛
z ⎞ −n
z
F ( z ) = e h ( z ) z ∏ ⎜⎜1 − ⎟e
n =1 ⎝ (− n) ⎟⎠

∞ z
⎛ z⎞ −
= e h ( z ) z ∏ ⎜1 + ⎟e n
n =1 ⎝ n⎠

## Definition : Rank of infinite product

1
The smallest non negative integer k for which the series ∑|a k +1 converges
n =1 n |

∞ ⎛ z ⎞
is said to be rank of the infinite product. ∏ E ⎜⎜ a ; k n ⎟⎟
n =1 ⎝ n ⎠

## If k denotes the rank of infinite product and if we take k n = k ∀ n , then the

infinite product
∞ ⎛ z ⎞
∏ E⎜⎜ a ; k ⎟⎟ is called canonical product.
n =1 ⎝ n ⎠

## Definition : Exponent of convegence of zeros of an entire function

53

If F ( z) = eh( z ) .z m P( z) ...(1)

where P(z) is canonical product of rank k and A a non-empty set of non negative

## real members α such that

converges.

Then the number ρ = glb A is called the exponent of convegence of the zeros of

## Let | an |= rn (0 < r1 ≤ r2 ≤ ... ≤ rn ≤ ....; rn → ∞ ) then the exponent of convergence

is given by
1 log rn
= lim
ρc n→∞ log n
1
Example : If (i) | a |= n 2 log (ii) | an |=| a |n , | a |> 1 then find ρc.
n n

## Ans. (i) 2 (ii) 0 ∞ 2

F ( z ) 1= z 2 e z
∑ α
Definition : Genus and Exponential ndegree
=1 | a n | of an entire function :

## and h(z) is a polynomial of degre q ≥ 0 then non-negative integer p = max(k , q) is

called the genus of the entire function and q is said to be the exponential degree of F.

If P(z) is not of finite rank k, or if h(z) is not a polynomial, then F is said be of infinite

genus.

## Example : Find genus of the entire function

2
F ( z) = e z z 2 P( z)

h( z ) = z 2 is a polynomial of degree 2.

P( z ) = 1

∴ kn = k = 0

54

## If F(z) be an entire function and A is a positive constant such that

A
max | F ( z ) |= M (r ) < e r
| z| = r

for all sufficiently large value of r = |z|, then F(z) is caled an entire function of

finite order.

Alternatively

## F(z) is of finite orer if ∃ A > 0 such that

A
| F ( z ) |= 0 (e r )

K >0
A
or | F ( z ) |< K e r ;

A

## order is defined by ρ = inf{ A :| f ( z ) |< e r }M (r ) < e Br ρ

A

If there is not a positive constant A such that
A
| F ( z ) |< e r ∀ r large enough

## Definition : Type of entire function:

If F(z) is an entire function of finite order ρ and there exists a constant B >0 such

that

r large enough

## then F(z) is said to be of finite type and

ρ
σ = inf{B : M (r ) < eBr , r > R}
is called the type of F.

## If σ = 0, F is called minimum type.

55
ρ
If there is no B such that M (r ) < e Br , then F is called of infinite type (or

maximum type).

## exponential type σ : An entire function F is said to be of expontial type σ(σ < ∞)

if either the function is of order ρ =1 and type , or the function is of order less

then 1.

## then for given ε >0 we have

ρ+ε
M (r ) < e r ∀r large enough ...(2)

## Also, there are some z with arbitrary modulus for which

ρ−ε
M (r ) < e r ≤ σ log ρ ..(3)
log
M
ρ ) <M
=( rlim
r(
elog rlog
) M (r )
<ρ+ε (r =| z |)
→∞ r
rlog log r
Then (2) implies
log log M (r ) < (ρ + ε) log r

and (3) implies
log log M (r )
>ρ−ε ...(5)
log r

log log M (r )
∴ ρ−ε< <ρ+ε
log r

log log M (r )
⇒ ρ = lim
r →∞ log r

## Theorem : The type σ of an entire function of finite order ρ is given by

56

logM (r)
σ = lim
r →∞ rp
Proof : Since the entire function f(z) of finite order ρ is of type σ

Therefore
ρ
M ( r ) < e σr ...(1)

## then for given ε > 0, we have

ρ
M (r ) < e (σ+ ε ) r ∀ r large enough ...(2)
ρ
and M (r ) > e ( σ −ε ) r ...(3)

## Then (2) implies

log M (r )
<σ+ε ...(4)
rp
and (3) implies
log M (r )
>σ−ε ....(5)
rp
| z |≤ R
log M (r )
⇒ σ−ε< <σ+ε
rp
log M (r )
⇒ σ = lim
r →∞ rp
Theorem : Jensen Formula

## in those zeros being repeated according to their multiplicities, then

1 2π n
R

2π 0
log | f (Re iθ
) | d θ = log | f ( 0 ) | + ∑ log
| ak |
k =1

## Then if the function

a1 a 2 ...a n f ( z )
g ( z) = ...(1)
(a1 − z )(a 2 − z )...(a n − z ) f (0)
57

is dfined at the point a1 , a 2 ,..., a n then it becomes analytic in | z |< R ′ and does

not vanish analytic in this disc. Then there exists a function h(z) analytic in R'such that

## From (1) g(0) =1, we may coose h(0) =0 [from (2)]

h( z )
Then can be made analytic in | z |< R ′
z
If we consider C : z = Re iθ , 0 ≤ θ ≤ 2π then by the Cauchy-Gousrat theorem

1 h( z ) 1 h(Re iθ )
∫ ∫0 Re iθ Rie dθ = 0

dz =
2πi C + z 2πi

1
∫ h(Re

= )dθ = 0 ...(3)
2π 0

But Re h( z ) = log | g ( z ) |

## Taking real part of (3)

1 2π a1 .a 2 ......a n f (Re iθ )
∫ (a − Re iθ )...(a − Re iθ ) f (0) dθ = 0
log
2π 2 π 2π 0
1 1 1
1 n 2π n
⇒ 2π ∫0
log | f (Re iθ
) | dθ −
2π ∫0
log | f ( 0 ) | d θ + ∑ log | a k | dθ
2π k =1 ∫0

1 n 2π
− ∑ log | a k − Re iθ | dθ = 0
2π k =1 ∫0

1 2π 1 n

2π ∫0
log | f (Re iθ
) | d θ − log | f ( 0 ) | + ∑ log | a k | ×2π
2π k =1

1 n 2π 1
+ ∑ ∫
2π k =1 0
log
| a k − Re iθ |
dθ = 0

1 2π 1 n
⇒ 2π ∫0
log | f (Re iθ
) | d θ − log | f ( 0 ) | + ∑ log | a k | ×2π
2π k =1
58

⎛ ⎞
⎜ ⎟
n 2π
1 ⎜ 1 ⎟
+ ∑ ∫ log⎜ ⎟dθ = 0
2π k =1 0 a e−iθ
⎜ | Re | k

−1 ⎟⎟
⎜ R
⎝ ⎠

1 2π 1 n

2π ∫0
log | f (Re iθ
) | d θ − log | f ( 0 ) | + ∑ log | a k | ×2π
2π k =1

1 n ⎡ ⎤

ak e−iθ
+ ∑ ⎢
2π k =1 ∫0 ⎣
− log | R | − log1 −
R
⎥dθ = 0

1 2π 1 n

2π ∫0
log | f (Re iθ
) | d θ − log | f ( 0 ) | + ∑ log | a k | ×2π
2π k =1

1 n 1 n ak e−iθ
+ ∑ 2π (− log R) − ∑ ∫ log1 − dθ = 0
2π k =1 2π k =1 0 R

1 2π 1 n
⇒ ∫
2π 0
log | f (Re iθ ) | dθ − log | f (0) | + ∑ log | a k | ×2π
2π k =1

n 2π
1 a k e − iθ
+ (− n) log R −

∑ ∫
k =1 0
log 1 −
R
dθ = 0
14 4244 3
( = 0 when |a k / R|≤1)

2π n n
1
∫ log | f (Re ) | dθ = log | f (0) | −∑ log | ak | + ∑ log R

⇒ 2π 0 k =1 k =1
n ⎛ R ⎞
= log | f (0) | + ∑ log⎜⎜ ⎟
k =1 ⎝ | ak | ⎟⎠
Corollary : If n(r) denotes the number of zeros of the entire function F(z) in the

## disc | z |≤ r , and F (0) ≠ 0, then

R
n(t )
∫ t
dt ≤ log M ( R ) − log | F (0) |
0

Proof : Let a1 , a 2 ,...., a n are zeros of F(z) in |z| <R such that | a1 |<| a 2 |< .... <| a n |

Then
n ⎛ R ⎞ n
∑ log⎜⎜ | a ⎟⎟ = n log R − ∑ log | a k |
k =1 ⎝ k |⎠ k =1
59

n −1
= n log R + ∑ k[log | a k +1 | − log | a k |] − n log | a n |
k =1

n −1 |a k +1 |
1
=∑ ∫ k dt + n(log R − log | a n |)
k =1 |a k | t

n −1 |a k +1 | R
k 1
=∑ ∫ dt + n ∫ dt ....(1)
k =1 |a k | t | an | t

n(t ) = 0 for 0 ≤ t ≤| a1 |

## n(t ) = n when | an |≤ t < R

We have (from 1)

( n − 1)
n |a | |a | |a | |a |
R
R 2
1 3
2 4
3 n
1
∑ log = ∫ dt + ∫ dt + ∫ dt + ... + ∫
| a k | |a1 | t
dt + n ∫ dt
k =1 |a 2 | t |a 3 | t |a n −1 | t | an | t

R
n(t )
=∫ dt
0 t

## Then by Jesens formula ρ c (2r ) < exp{(2r ) ρ+ε / 3 }

M
R
n (t ) 1 2π iθ
∫ t dt =
2 π ∫ log | F (Re )dθ − log | F (0) |
0 0

## monotonic increasing with t

2r 2r 2r
n (t ) n(t ) dt
∴ ∫ t dt ≥ ∫ t dt ≥ n ( r ) ∫ t = n(r ) log 2
0 r r

1 2 r n (t )
log 2 ∫0 t
⇒ n(r ) ≤ dt ....(1)

60

## Replacing R by 2r in last result of the corollary and using (2)

2r
n(t )
∫ dt < r ρ + 2ε / 3 − log | F (0) |< r ρ+ ε ...(3)
0 t

## (1) and (3)

1 ρ +ε
n( r ) < r ...(4)
log 2

⇒ n(r) = o(r ρ +ε ) as r → ∞
Now we show that

## Let ε be such that and r = rn

1 ρ+ ε
n = n(rn ) < rn ....(5)
log 2 0∞c<≤ε1ρ< δ
ρ
∑ r ρ+ε
for all r large enough n =1 n

from (5)
1 1 1
<
rnρ + ε n log 2
( ρ +δ ) /( ρ + ε )
1 1 ⎛ 1 ⎞
and <A A = ⎜⎜ ⎟⎟
rnρ +ε n( ρ +δ ) /( ρ +ε ) ⎝ log 2 ⎠
(ρ + δ ) ∞
1
(ρ + ε )
> 1 , the series ∑n ρ δ
n=1
( + ) /( ρ +ε ) converges

Hence ∑ rn−(ρ+ε)
n =1

## Theorem : Suppose that about each zero a n , | a n |> 1, of a cononical product

61

1
P(z), a dix of radius r p is described where rn = | a n | and = order P(z). Then in
n

the region R complementary to the union of all those discs, the inequality

## holds an infinitely many circles of radii arbitrarily large.

∞ 1
Proof : It is obivious that the sum 2 n∑=1 r p infinite as ( p > ρ = ρ c ) the union of
n

−p −p
the intervals U [ rn − rn , rn + rn ] on the real axis each of length 2rn− p does not cover
n

## the entire positive real axis.

There are infinitely many circles with center at the origin and radii arbitrarily large

which lie in R.

## k = rank of P(z), then

⎛ z ⎞ ⎛ z ⎞
| P ( z ) |= ∏ E ⎜⎜ a ; k ⎟⎟ ∏ E ⎜⎜ a ; k ⎟⎟ ....(1)
rn ≤ 2 r ⎝ n ⎠ rn > 2 r ⎝p >n ρ ⎠ ρ +ε
| P( z ) |> e − r (ε > 0)
⎛ z ⎞ ⎛ z ⎞
⇒ log | P ( z ) | = ∑ log E ⎜⎜ a ; k ⎟⎟ + ∑ log E ⎜⎜ a ; k ⎟⎟
rn ≤ 2 r ⎝ n ⎠ rn > 2 r ⎝ n ⎠
k
z z ⎛ z ⎞ 1 ⎛ z ⎞
≥ ∑ log 1 − −∑ + .... + ⎜⎜ ⎟⎟ . − ∑ log E ⎜⎜ ; k ⎟⎟ ....(2)
rn ≤ 2 r an rn ≤ 2 r an ⎝ an ⎠ k rn > 2 r ⎝ an ⎠

## For |z| =r and rn ≤ 2r , we obtain

⎛ z ⎞ ⎧⎪ 1 ⎛ a ⎞ ⎫⎪
2 k k −1 k −1
k
z 1⎛ z ⎞ 1⎛ z ⎞ 1 ⎛ an ⎞
+ ⎜⎜ ⎟⎟ + ..... + ⎜⎜ ⎟⎟ ≤ ⎜⎜ ⎟⎟ ⎨ + ⎜ ⎟ + .... + ⎜ n ⎟ ⎬
an 2 ⎝ an ⎠ k ⎝ an ⎠ ⎝ an ⎠ ⎪⎩ k k − 1 ⎝ z ⎠ ⎝ z ⎠ ⎪⎭

⎧⎪ 1 k −1
⎫⎪
k
⎛ r ⎞ an
≤ ⎜⎜ ⎟⎟ ⎨ + .... + ⎬
⎝ rn ⎠ ⎪⎩ k z ⎪
1 4 42 4 4 3⎭
( A1 which does not depend on r )

k
⎛r ⎞
= A1 ⎜⎜ ⎟⎟ ....(3)
⎝ rn ⎠
62

k k
z 1⎛ z ⎞ ⎛ r ⎞
∴ ∑ + ....... + ⎜⎜ ⎟⎟ ≤ A1 ∑ ⎜⎜
k ⎝ an ⎠
⎟⎟
rn ≤ 2 r an rn ≤ 2 r ⎝ rn ⎠

2 ρ + ε / 2− k .r ρ + ε / 2+ k
= A1 ∑ ρ+ ε / 2−k .r ρ+ε / 2 (r ) k
rn ≤ 2 r 2 n

2 ρ + ε / 2− k .r ρ+ ε / 2
= A1 ∑ ρ+ε / 2−k
.(rn ) k
rn ≤ 2 r ( 2r )

1
= A1 2 ρ + ε / 2 − k .r ρ + ε / 2 ∑ (rn ) ρ+ε / 2−k
.(rn ) k
rn ≤ 2 r

⎛ 1 ⎞
= r ρ + ε / 2 ⎜⎜ A1 2 ρ + ε / 2 − k ∑ ρ + ε / 2 ⎟⎟
⎝144 42n4 4 43⎠
=1 rn

## ( A2 which does not depend on r )

= A2 r ρ + ε / 2 ....(4)

If k =0 the sum in (4) does not appear in (2). For z outside every circle | z − an |= rn− p

with rn ≤ 2r .

We have

z | a − z | rn− p
1− = n = = rn− p −1 ≥ (2r ) − p −1
an | an | rn
Hence for all circles |z| =r in the region R, with r sufficiently large,
ρ+ε
log | P ( z ) |> − r ρ + ε ⇒ | P ( z ) |> e − r
63

## F(z) = eh( z) zmP(z) is always possible where h(z) is a polynomial of degree ≤ ρ, m≥ o

is the multiplicity of z =0 and P(z) is a canonical product of rank .

## can be factorize in the following from

...(1)

When h(z) is an entire function and P(z) a product which may or may not be

canonical.

## By the previous theorem ρc ≤ ρ , so that P(z) is of finite rank k ≤ ρ .

ρ+ ε
Also since | P ( z ) |> e − r

replacing ε by we have

|≤
FεPρ
((zz))=|>eeh(−zr) z m P( z)
ρ+ ε / 2

## on infinitely many circles |z| =r of arbitrarily

ρ+ε / 2
Aslo | F (z) |< er is satisfied for all values of r sufficiently large, since F is

## suppose to be of order ρ. Then it follows that

ρ+ ε / 2
| F (z) | er
e Re h ( z )
=| e h( z )
|= m < ρ+ ε / 2
| z P( z ) | e − r
ρ+ε / 2 ρ+ε
= e 2r < er on circles of arbitrarily large radius.

## Hence on such circles

Re h( z ) < r ρ + ε

## ⇒ h(z) is a polynomial of degree not greater then ρ.

⎛ z2 ⎞
Example : Show sin πz = πz ∏ ⎜⎜1 − 2 ⎟⎟ by Hadaward Factorization Theorem.
n =1 ⎝ n ⎠

sinπ z ∞ π 2n z n
Solution : Let F ( z) = = ∑ (−1)n ....(1)
π z n =0 (2n + 1)!
64

π2 z
=1− + .....
3!

when F ( z ) = ∑ c n z then by the formula
n

n =0

1 log(1 / | c n |)
= lim ...(2)
ρ n→∞ n log n

1 1
= 2 i.e. ρ = ...(3)
ρ 2
Since zeros of F(z) are z =1, 4, ..., n2, ... we have

sin π z ∞
⎛ z ⎞
F ( z) = = e h ( z ) ∏ ⎜1 − 2 ⎟ ...(4)
π z n =1 ⎝ n ⎠

## of degee ≤ order of F(z) i.e. degree of

⇒ h( z ) = C (constant)
∞ 1
⎛ z⎞ h( z ) ≤
∴ F (z) = e ∏⎜1− 2 ⎟
C
2
n=1 ⎝ n ⎠
Since F (0) = 1

⇒ C =0

sin π z ∞
⎛ z ⎞
∴ = F ( z ) = ∏ ⎜1 − 2 ⎟
π z n =1 ⎝ n ⎠

Replacing z by z2

sin πz ∞ ⎛ z2 ⎞
= ∏ ⎜⎜1 − 2 ⎟⎟
πz n =1 ⎝ n ⎠
65